Randomized Phase II Trial of Sulindac, Atorvastatin and Prebiotic Dietary Fiber for Colorectal Cancer Chemoprevention - Limburg, Paul J. (2011)
Sulindac, atorvastatin or prebiotic dietary fiber may reduce colorectal cancer (CRC) risk. However, clinical trial data are currently limited. We conducted a randomized, phase II chemoprevention trial involving subjects age ≥ 40 years, with previously resected colon cancer or multiple/advanced colorectal adenomas. Magnification chromoendoscopy (MCE) was performed to identify and characterize rectal aberrant crypt foci (ACF); eligibility criteria required ≥ 5 rectal ACF at baseline. Intervention assignments were: (A) atorvastatin 20 mg qd; (B) sulindac 150 mg bid; (C) oligofructose-enriched inulin (as ORAFTI(®)Synergy1) 6 gm bid; or (D) control (maltodextrin) 6 gm bid, for 6 months. Percent change in rectal ACF number (%ΔACF) within arm was the primary endpoint. Secondary endpoints included changes in proliferation (Ki67) and apoptosis (caspase-3), as measured from normal mucosa biopsy samples. Among 85 eligible randomized subjects, 76 (86%) completed the trial per protocol. The median (range) of rectal ACF was 9 (5–34) and 8 (0–37) at baseline and post-intervention, respectively. The median (standard deviation) for %ΔACF was 5.6 (−69–143%), −18.6 (−83–160%), −3.6 (−88-83%) and −10.0 (−100–117%) in the atorvastatin, sulindac, ORAFTI(®)Synergy1 and control arms, respectively. Neither within arm (p=0.12–0.59) nor between arm (p=0.30–0.92) comparisons of %ΔACF were statistically significant. The active and control interventions also appeared to have similar effects on mucosal proliferation and apoptosis (p > 0.05 for each comparison). Data from this multi-center, phase II trial do not provide convincing evidence of CRC risk reduction from six month interventions with atorvastatin, sulindac or ORAFTI(®)Synergy1, although statistical power was limited by the relatively small sample size.